Optimasi Perencanaan Produksi Kue Dan Bakery di Home Industry â€œSELARAS CAKEâ€ Menggunakan Model Goal Programming - Nusaibah Al Istiqomah; Dwi Lestari (Jurnal Fourier, 2017)
This study aimed to: know the model of the production planning problem solving goal programming model without the priority objectives and goal programming model of the priority goals, determine the demand forecast cakes and bakery as well as to determine which is optimal between the two models in determining the amount of production. This research was conducted in bakery products such as cakes and banana muffins, brownies, sponge rollers, greenis, bakery and chocolate pizza bakery. By reviewing of some of the literature, this problem can be solved by using a goal programming models and models without priority objectives programminng goal with the priority goal. Based on the research, production plans generated from both models is identical, ie the amount of production of banana muffins as many as 31 586 units, greenis as many as 31 839 units, sponge rollers as many as 31 839 units, brownies as many as 60645 units, chocolate bakery as many as 16 425 units, and pizza bakery as many as 164 245 units , Meanwhile, on the model of goal programming without priority objectives the company obtained revenue of Rp 426,034,500.00 with a production cost of US $ 147,021,000.00, while the advantages of goal programming models with a priority goal of Rp 376,759,500.00 and production costs Rp 131,006,600.00. This means, if the profit is assumed to revenue minus production costs, then for a greater profit, the company suggested using the model of goal programming without priority objectives for yield greater reductions.